The influence of e-banking service quality on customer loyalty: A moderated mediation approach. Issue 5 (1st July 2019) - Shankar, Amit; Jebarajakirthy, Charles
Abstract : Purpose: Providing high-quality e-banking services is considered a basic strategy for attracting and retaining customers with electronic-banking platforms. The purpose of this paper is to empirically investigate a comprehensive moderated mediated mechanism for enhancing customer loyalty toward e-banking platforms via e-banking service quality (EBSQ) practices. Reliability, website design, privacy and security and customer service and support are the dimensions of EBSQ. Design/methodology/approach: Data were collected through structured questionnaires from a sample of 1, 028 e-banking users in India. To test the hypotheses, a structural equation modeling approach was used. Findings: The findings showed that of the EBSQ dimensions, reliability along with privacy and security enhanced customer loyalty to e-banking. The initial trust in e-banking mediates the effects of EBSQ dimensions on customer loyalty except for website design. The mediation effects of initial trust varied between high and low-involved consumers. Research limitations/implications: This study was conducted with e-banking users in one country using cross-sectional data. Hence, the model should be replicated among e-banking users in other countries and with the longitudinal data. Practical implications: Establishing a loyal customer base is an important goal for banks. This study demonstrates which specific EBSQ dimensions banks should emphasize to enhance consumers' initial trust and loyalty toward e-banking services. Originality/value: This study suggests a moderated mediated mechanism for enhancing customer loyalty to e-banking, which incorporates initial trust as a mediator and consumer involvement as a moderator. It applies cognitive-motivation-relational theory to link EBSQ dimensions with customer loyalty. Thus, this study enables a better understanding of this theory in the e-banking context.